Designing a Collaborative Learning Model for Reading in Government Education: A Lifelong Learning Perspective - Kurniawati, Layla; Pradana, Satria Adi; Yudha, Galang Tirta; Kulacai, Waiphot; Wahyono, Edi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study focuses on the design and implementation of a collaborative learning model aimed at enhancing reading comprehension among first-year students at the Institute of Public Administration (IPDN) in Indonesia. The model was specifically developed to address challenges in a higher education boarding school environment, including limited access to technology and the transition to online learning. A mixed-methods approach was employed, involving 141 students organized into small groups of 3-4 members, mixing higher and lower achievers to encourage diverse interactions. The study examines how this model promotes student engagement, independence, and collaborative problem-solving skills—key components for lifelong learning. Data collection involved online questionnaires, interviews, and reading comprehension tests, which were analyzed using thematic coding and descriptive statistics. The results demonstrate significant improvements in reading comprehension, expanded vocabulary related to government concepts, and the emergence of student leaders who facilitated group learning. Additionally, the model was wellreceived by students, enhancing their independence and fostering a collaborative learning environment. The findings emphasize the potential of this model to support lifelong learning by developing essential skills that extend beyond the classroom, thereby promoting both academic achievement and personal growth.